Arrhythmias and electrocardiographic findings in Coronavirus disease 2019: A systematic review and meta‐analysis. Issue 6 (18th May 2021) - Garcia‐Zamora, Sebastian; Lee, Sharen; Haseeb, Sohaib; Bazoukis, George; Tse, Gary; Alvarez‐Garcia, Jesus; Gul, Enes Elvin; Çinier, Göksel; Alexander, Bryce; Martins Pinto‐Filho, Marcelo; Liu, Tong; Baranchuk, Adrian
Abstract: Background: Coronavirus disease 2019 (COVID‐19) primarily causes lung infection, but recent studies have shown that cardiac involvement is associated with a worse prognosis. Objectives: We conducted a systematic review and meta‐analysis to examine the prevalence of cardiac arrhythmias detected by the electrocardiogram and their relationships with adverse outcomes in patients with COVID‐19. Methods: PubMed and Google were searched for studies that reported on cardiac arrhythmias and/or examined the relationship between arrhythmias and adverse outcomes. Results: Thirty studies with 12, 713 participants were included in the systematic review, and 28 studies ( n  = 12, 499) in the meta‐analysis. The mean age was 61.3 ± 16.8 years; 39.3% were female. In 25 studies with 7578 patients, the overall prevalence of cardiac arrhythmias was 10.3% (95% confidence interval [CI]: 8.4%–12.3%). The most common arrhythmias documented during hospitalization were supraventricular arrhythmias (6.2%, 95% CI: 4.4%–8.1%) followed by ventricular arrhythmias (2.5%, 95% CI: 1.8%–3.1%). The incidence of cardiac arrhythmias was higher among critically ill patients (relative risk [RR]: 12.1, 95% CI: 8.5–17.3) and among non‐survivors (RR: 3.8, 95%, CI: 1.7–8.7). Eight studies reported changes in the QT interval. The prevalence of QTc > 500 ms was 12.3% (95% CI: 6.9%–17.8%). ST‐segment deviation was reported in eight studies, with a pooled estimate of 8.7% (95% CI: 7.3% to 10.0%). Conclusion: Our meta‐analysis showed that QTc prolongation, ST‐segment deviation, and various other cardiac arrhythmias were observed in patients hospitalized with COVID‐19. The presence of cardiac arrhythmias was associated with a worse prognosis.